The influence of hip muscle strength on gait in individuals with a unilateral transfemoral amputation - Heitzmann, Daniel; Leboucher, Julien; Block, Julia; Putz, Cornelia; Götze, Marco; Wolf, Sebastian Immanuel; Alimusaj, Merkur (PLOS ONE, 2020)
Introduction: A unilateral transfemoral amputation (TFA) has a major impact on function. A leg-length discrepancy is the primary structural change, accompanied by the loss of lower-limb muscle volume and function. Prostheses can help individuals with a TFA to regain function, but such individuals still do not reach the functional level of unimpaired peers and exhibit gait deviations. This study gives insight into the causality between residual limb strength and gait deviations in individuals with a TFA. Methods: A convenient sample of 13 male individuals with a TFA (38.0 ± 12.6y; 179.7cm ± 6.5cm; 82.9kg ± 12.4kg) was recruited for this study. One participant with TFA was excluded, as he differed from the rest of the cohort, in residual limb length and the use of walking aids. A cohort of 18 unimpaired subjects served as a reference group (REF; nine females; 44y ± 13y; 174cm ± 9cm; 71kg ± 12kg). All participants underwent a conventional clinical gait analysis using a marker based 3D motion capture system and force platforms. Kinematics and kinetics were determined utilizing standard modelling methods. All subjects underwent a strength test, using a custom-made device to determine isometric moments of the hip joint in abduction, adduction, extension, and flexion. Peak values for maximum isometric moments for each movement direction and selected kinematic and kinetic values were derived from the results. Differences between subjects with TFA and unimpaired were compared using a Mann-Whitney U Test and associations between groups by Spearman’s rank correlation. Results: The participants with a TFA showed a significantly lower maximum isometric moment for hip abduction (0.85 vs. 1.41 Nm/kg p < .001), adduction (0.87 vs. 1.37 Nm/kg p = .001) and flexion (0.93 vs. 1.63 Nm/kg p = .010) compared to the reference group. Typically reported gait deviations in people with a TFA were identified, i.e. significant lower cadence and increased step width. We further identified altered coronal plane hip and trunk kinematics, with significantly higher ranges of motion during involved side stance-phase. Gait kinetics of individuals with a TFA showed significantly lower peak values during stance for hip abduction, adduction and extension moments in comparison to the reference group. We identified a moderate negative correlation between maximum isometric moment for hip abduction and trunk obliquity range of motion (ρ = -0.45) for participants with a TFA, which was not significant (p = 0.14). Conclusion: We showed that there are strength deficits in individuals with TFA and, that there are moderate correlations between gait deviations, i.e. lateral trunk lean during involved side stance and isometric hip abductor moment. The relation between maximum moments during gait and the corresponding maximum isometric moment may therefore be helpful to detect strength related compensation mechanisms. However, the moderate, non-significant correlation between lateral trunk lean and isometric hip abductor moment was the only one which corresponded directly to a gait deviation. Thus results must be interpreted with care. This study suggests that gait deviations in individuals with TFA are multifactorial and cannot be exclusively explained by their strength deficits. Future studies should explore the relationship between strength with kinematics and kinetics during gait in this population.
Gesehen am 09.11.2020